2008
DOI: 10.1589/jpts.20.233
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial on the Treatment of Chronic Rhinosinusitis with Continuous Ultrasound

Abstract: Abstract.[Purpose] Chronic rhinosinusitis is a common and long-term disease for which no definitive treatment has been established. The purpose of this trial was to examine the effects of continuous ultrasound on the treatment of patients with chronic maxillary and frontal sinusitis.[Subjects] Thirty adults with chronic rhinosinusitis (24 men, 6 women; age range, 18-65 yrs; mean, 35

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Our findings are similar to those of Naghdi et al 12 and Ansari et al 9,10 who showed that the frequency of the main symptoms in chronic rhinosinusitis (facial pain, nasal congestion and nasal block, rhinorrhea, olfaction disorders, and coughing) decreased significantly following 1 and 3 MHz LIUST. These studies showed that the thickness of the sinus mucosa decreased, the meatal ostia became more open, and paranasal sinus lesions regressed after the 15 th day of LIUST at 1.0 W.cm -2 (SATA) for 5 minutes over the maxillary and frontal sinuses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are similar to those of Naghdi et al 12 and Ansari et al 9,10 who showed that the frequency of the main symptoms in chronic rhinosinusitis (facial pain, nasal congestion and nasal block, rhinorrhea, olfaction disorders, and coughing) decreased significantly following 1 and 3 MHz LIUST. These studies showed that the thickness of the sinus mucosa decreased, the meatal ostia became more open, and paranasal sinus lesions regressed after the 15 th day of LIUST at 1.0 W.cm -2 (SATA) for 5 minutes over the maxillary and frontal sinuses.…”
Section: Discussionsupporting
confidence: 92%
“…These studies showed that the thickness of the sinus mucosa decreased, the meatal ostia became more open, and paranasal sinus lesions regressed after the 15 th day of LIUST at 1.0 W.cm -2 (SATA) for 5 minutes over the maxillary and frontal sinuses. 10,12 Studies by Barros et al 11 demonstrated that only two sessions of pulsed mode LIUST at 1.0 -1.5 W.cm -2 for 3 minutes were not enough to decrease nasal block in 13 subjects with rhinosinusitis -with or without antibiotics. However, this approach significantly reduced other symptoms such as headaches and facial pain in these subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies that used 1-MHz frequencies to treat CRS symptoms, including pain [38][39][40][52][53][54][55], but only one was conducted in English with comparable data. We obtained raw data for this study; it had a total of 20 patients treated with a 1-MHz frequency (1 W/cm 2 and 0.5 W/cm 2 ) at a 10% duty cycle [40].…”
Section: Analysis Of Previously-published Datamentioning
confidence: 99%